Beyond Pharmacotherapy: Investigating the Role of Classical Music in Preoperative Anxiety Management for Cesarean Sections - Manurung, Hormat Janner; Handoko Tri Kuncoro (Open Access Indonesian Journal of Medical Reviews, 2024)
Preoperative anxiety is a prevalent concern among women undergoing cesarean sections (C-sections), potentially impacting maternal and neonatal outcomes. While pharmacotherapy is commonly used to manage anxiety, non-pharmacological interventions like music therapy offer a promising alternative or adjunct. This study aimed to investigate the efficacy of classical music in reducing preoperative anxiety levels in women scheduled for C-sections. A randomized controlled trial was conducted involving 100 women scheduled for elective C-sections. Participants were randomly assigned to either the intervention group (classical music listening) or the control group (standard care). Anxiety levels were assessed using the State-Trait Anxiety Inventory (STAI) before and after the intervention. Physiological parameters such as heart rate and blood pressure were also monitored. The intervention group demonstrated a significant reduction in both state and trait anxiety scores compared to the control group (p < 0.05). Additionally, the intervention group exhibited lower heart rate and blood pressure levels post-intervention. In conclusion, classical music listening can be an effective non-pharmacological intervention for reducing preoperative anxiety in women undergoing C-sections. The findings suggest that integrating music therapy into standard preoperative care may enhance patient well-being and contribute to improved surgical outcomes.